PENGELOLAAN SANITASI LINGKUNGAN DALAM PEMBANGUNAN DAERAH DI KOTA SERANG - Anita Widiastuti (Jurnal Ekonomi-Qu, 2019)
One of the Sustainable Development Goals (TPB) Agenda is to ensure the availability and management of clean water and sustainable sanitation. The city of Serang as the provincial capital has an important role in the development of Banten Province, so that the regional spatial development policy must be able to prioritize the quality of environmentalsanitation. This research uses descriptive qualitative research methods. The results of this study indicate that by considering weaknesses, strengths, opportunities and threats, the most appropriate environmental sanitation development policy in Serang City is to optimize the strengths to overcome external problems in Serang City. Recommendations submitted forthe development of environmental sanitation are to improve the quality of sanitation facilities and infrastructure, increase the promotion of hygiene and health and improve the quality of health services.